Efektifitas Terapi Bermain English Fun untuk Meningkatkan Kemampuan Kognitif Anak Prasekolah Dimasa Pandemi Covid-19: The Effectiveness of English Fun Play Therapy to Improve Cognitive Ability of Preschool Children During the Covid-19 Pandemic - Eka Adimayanti; Dewi Siyamti; Endang Susilowati; Deya Purnamasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2022)
Preschool-aged children enter the pre-operational stage of development where children have prominent characteristics that combine and transform information. Preschool age is the optimal period for children to start showing interest in health, children experience language development and interact with the social environment. Cognitive abilities that can be developed through play activities include the ability to recognize, remember, think convergently, diverge, and give judgments. This study aims to determine the effectiveness of English Fun play therapy on the cognitive abilities of preschool age children. This research is a Quasi Experimental Design with Pretest-Posttest Non Equivalent Design. Respondents of this study were preschoolers aged 66 months-72 months as 60 students who were observed using the Developmental Pre Screening Questionnaire (KPSP) instrument according to their development when nurses did therapy playing English fun. Based on the results of the study, there was a significant difference between the initial cognitive ability score and the final cognitive ability score of 3.33. It can be concluded that the results of monitoring cognitive abilities in preschool age children increased after playing therapy with the English fun game method. It is hoped that the play therapy method in English can be continued to be included in the additional curriculum or extra curriculum so that it can improve children's cognitive abilities and children's creativity. ABSTRAKAnak Usia prasekolah memasuki tahap perkembangan pra operasional dimana mempunyai karakteristik menonjol anak telah mengkombinasi dan mentransformasi informasi. Usia prasekolah merupakan periode yang optimal bagi anak untuk mulai menunjukkan minat dalam kesehatan, anak mengalami perkembangan bahasa dan berinteraksi terhadap lingkungan sosial. Kemampuan kognitif yang dapat dikembangkan melalui kegiatan bermain antara lain adalah kemampuan mengenal, mengingat, berfikir konvergen, divergen, memberi penilaian. Penelitian ini bertujuan untuk mengetahui efektifitas terapi bermain english Fun terhadap kemampuan kognitif anak usia prasekolan. Penelitian ini merupakan penelitian Quasi Experimental Design dengan Pretest-Posttest Non Equivalent Design. Responden penelitian ini adalah usia prasekolah usia 66 bulan-72 bulan sebanyak 60 siswa yang diobservasi menggunakan instrument Kuesioner Pra Scrining Perkembangan (KPSP) sesuai dengan userkembanganya ketika perawat melakukan terapi bermain english fun. Berdasarkan hasil penelitian menunjukkan ada perbedaan yang bermakna antara skor kemampuan kognitif awal terhadap skor kemampuan kognitif akhir sebanyak 3.33. Dapat disimpulkan bahwa hasil pemantauan kemampuan kognitif pada anak usia prasekolah meningkat setelah dilakukan terapi bermain dengan metode permainan english fun. Diharapkan metode terapi bermain dalam bahasa inggris dapat dilanjutkan untuk di masukkan ke kurikulum tambahan atau kurikulum ekstra sehingga dapat meningkatkan kemampuan kognitif anak dan kreatifitas anak.